On the status of Statice dianiae Pau (Plumbaginaceae) - Jaume X. Soler (Anales del Jardín Botánico de Madrid, 1997)
An apomictic Limonium with a single pollen-stigma combination (B type), Limonium interjectum, is proposed as a new species to replace the invalid name Statice dianiae Pau. The new species has a restricted distribution on the sea costs of eastern Spain (Alicante Province). It shows a striking morphological similarity to L. virgatum (Willd.) Fourr. and L. girardianum (Guss.) Girard; on this basis it is suggested that L. interjectum is a hybrid derived from the two species.